IDENTIFIKASI BAKTERI PADA PRODUK DARAH THROMBOCYTE CONCENTRATE - Rahmatullah, Widia; Dewi Lukita Sari, Ana; Azimata Rosyidah, Rudina; Kuswandari, Roselina; Muflih, Arifin; Handayani, Reska (Institut Kesehatan dan Teknologi Al Insyirah, 2024)
TThe Thrombocte Concentrate component is the blood component that is most easily contaminated with bacteria due to its processing and storage at room temperature. Blood or blood products that are ready to be transfused must be safe and free from the risk of infection by infectious diseases and contamination by microorganisms. Sources of bacterial contamination can come from donor skin that is less than aseptic, donor bacteremia and processing of blood products. This type of research is Pre-Experiment. The design of this research is One-Shot Case Study. In One-Shot Case Study design. The sample in this study used 1 Thrombocyte Concentrate blood product. Then it was replicated into 10 samples for Nutrient Agar media and 10 samples for Mac conkey Agar media. From the results of research conducted on 10 samples of Nutrient Agar (NA) media, it was found that there was bacterial growth in all petri dishes on Nutrient Agar (NA) media. ), while in petri dish number 10 it was found that 10% of gram-positive bacteria were in the form of bacilli (rods). From the results of research conducted on 10 samples of Mac Conkey Agar (MCA) media, no bacterial growth was found in all of the MCA media petri dishes. There was contamination of Gram-Positive bacteria in the form of Cocci (Rounds) and Bacillus (Sticks) in Thrombocyte Concentrate blood products using NA media in 10 samples out of the total samples examined were 10 samples of NA media. There was no Gram-Negative bacterial contamination in Thrombocyte Concentrate blood products using MCA media in 10 samples from the 10 samples examined.